Moral and Cognitive Aspects of Aesthetic Experience. In the Face of Contemporary Aestheticization Processes - Ziółkowska-Juś, Anna (Sensus Historiae, 2022)
The article points to an integral aesthetic experience in which the ethical, aesthetic and cognitive spheres complement each other but do not reduce one to another. Such an approach to aesthetic experience can be found in contemporary hermeneutic reflection and pragmatic aesthetics. However valuable the distinction between the moral, cognitive and aesthetic spheres is, the recognition of their mutual autonomy leads to the disintegration of human experience, identity and culture. Integral aesthetic experience can counteract the negative consequences of cultural aestheticization, which reduces the cognitive and moral realms to the aesthetic one.